Anxiety Sensitivity Index-3 Suicidal Cognition Concerns: A New Measure Examining Negative Reactions to Suicidal Ideation. Issue 1 (2nd January 2022) - Smith, Nicole S.; Bauer, Brian W.; Martin, Rachel L.; Tucker, Raymond P.; Capron, Daniel W.
Abstract: Objective: Anxiety sensitivity cognitive concerns (ASCC), the fear of the consequences of mental dyscontrol, has been established as a risk factor for suicidal ideation (SI). Treatments targeted at reducing ASCC have been shown to reduce suicide risk. In this study, a new self-report measure, the Anxiety Sensitivity Index-3 Suicidal Cognition Concerns (ASI-3-SCC), was developed to assess sensitivity specifically to thoughts of suicide and wanting to die. Method: Participants completed the new measure as well as measures of anxiety sensitivity, depressive symptoms, SI, and worst point SI. We hypothesized that the ASI-3-SCC would be associated with SI and worst point SI. Additionally, we hypothesized that the ASI-3-SCC would moderate the relationship between ASCC and SI. Results: As predicted, the ASI-3-SCC was significantly associated with SI in the past two weeks and lifetime worst point SI after accounting for ASCC and depression. The ASI-3-SCC also moderated the relationship between ASCC and SI such that ASCC was related to SI at high levels of ASI-3-SCC. Conclusions: We suggest that the interpretation of SI and feelings of wanting to die as dangerous may lead to more attention to those thoughts when they occur and increased psychological distress associated with those thoughts. This measure will allow researchers to measure a novel construct in the literature and further examine the impact of catastrophic interpretations of suicidal thoughts. Highlights: Created a new measure for sensitivity to thoughts of suicide and wanting to die. Suicidal cognition concerns associated with suicidal ideation in the past two weeks. Suicidal cognition concerns associated with lifetime worst point suicidal ideation. Suicidal cognition concerns moderated AS cognitive concerns and ideation relation.